The arylstibonic acid compound NSC13746 disrupts B-ZIP binding to DNA in living cells - Heyerdahl, Sarah L. (Eur J Cell Biol, 2010)
The inhibition of DNA binding of basic leucine zipper (B-ZIP) transcription factors is a clinically relevant molecular target. Our laboratory has previously reported two methods of inhibiting B-ZIP DNA binding in solution: 1) an arylstibonic acid compound that binds to the basic region, stabilizes the B-ZIP dimer, and prevents B-ZIP DNA binding and 2) dominant negative proteins, termed A-ZIPs, that heterodimerize with B-ZIP domains in a leucine zipper-dependent manner. To determine if these two agents also inhibit DNA binding in live cells, GFP-tagged B-ZIP domains and mCherry-tagged A-ZIP domains were transfected into NIH3T3 cells to assess protein localization and Fluorescence Recovery After nuclear Photobleaching (FRAP). FRAP, showed that all six GFP-B-ZIP domains examined recovered faster in the nucleus in the presence of drug that we interpret represents an inhibition of DNA binding. Faster recovery in the presence of the A-ZIP was leucine zipper dependent. The arylstibonic also induced a cytoplasmic localization of all B-ZIP domains while the A-ZIPs induced a leucine zipper-dependent cytoplasmic localization. Thus, the change in cellular localization of B-ZIP domains could be used as a high-throughput assay for inhibitors of B-ZIP DNA binding. Additionally, the arylstibonic acid compound was cytostatic in clear cell sarcoma cells, which express a chimera between the B-ZIP domain of ATF-1 and N-terminal activation domain of EWS but not in K562 cells that express a non-B-ZIP containing chimeric protein BCR-ABL. These studies suggest that arylstibonic acid compounds or other small molecules capable of inhibiting B-ZIP DNA binding could be valuable anticancer agents.